Jesus Christ Superstar. - Jewison, Norman (Universal Pictures and Robert Stigwoop, 1973)
This dazzling interpretation of the Tim Rice Andrew Lloyd Webber rock opera tells the story of Christ's (Ted Neely) final weeks in a bold and epic production. Shot entirely on location in Israel, producer-director Norman Jewison creates a brilliant example of modern movie making with groundbreaking vision and the un-forgettable songs and music of Rice and Webber. Nominated for several Golden Globe Awards including Best Picture, Best Actor and Best Actress, this legendary classic is a collector's must-have in this spectacular Edition.